Green synthesis of biocompatible fluorescent carbon dots from bitter gourd for effective metal sensing and biological applications - V. Renuga; X. Vinoliya; A. Dinesh; S. Suthakaran; Manikandan Ayyar; V. Mohanavel; Lalitha Gnanasekaran; Prabhu Paramasivam; R. Bousbih; M. Khalid Hossain; A. Rajendran; S. Santhoshkumar (Sensing and Bio-Sensing Research)
Highly fluorescent Carbon dots (C-dots) were synthesized from the Bitter Gourd by simple hydrothermal method without the addition of any surfactant or additives. The optical properties, luminescence, phase formation and crystal structure were measured using UV–Visible spectroscopy (UV–Vis), Photoluminescence (PL), X-ray diffraction (XRD) and Transmission electron microscopy (TEM) by varying the medium from acidic to basic by changing its pH (2−12) and temperature range (180-300οC) to assess the exact nature and properties of the synthesized C-dots. The synthesized C-dots have wide range of applications from metal sensing to bioimaging and optoelectronics. The antimicrobial properties of the prepared C-dots were also analyzed using Klebsiellapneumoniae and Staphylococcus aureus microbes and found that the prepared C-dots have better antimicrobial activity in both microbes with better efficiency due to its smaller size. The challenges and perspectives of the synthesized C-dots from Bitter Gourd were also discussed.